Prevalence of Systemic Hypertension and Hypertensive Crises among Adult Outpatients in a Cardiac Hospital in Central Nepal - Laudari, Shankar; Gupta, Madhu; Dhakal, Abiona; Yadav, Raghuvendar; Upadhyay, Hari Prasad (Journal of National Heart and Lung Society Nepal, 2024)
Background: The prevalence of systemic hypertension is a significant global health concern, affecting a large population worldwide. The objective of the study was to determine the prevalence of systemic hypertension and hypertensive crises among adult outpatients in a cardiac hospital in central Nepal. Methods: This is a hospital based cross-sectional observational study conducted at outpatient department of Cardiology in central Nepal. Consecutive 487 patients were included in the study. All the patients had undergone proper blood pressure measurements as per the standard protocol with Aneroid Sphygmomanometer. Results: Out of 487 participants in the study, 199 were diagnosed as hypertensives. The prevalence of hypertension was 40.86%, out of whom 56.28% were males and 43.72% were females with male: female ratio of 1:1.28. Mean age of the patients was 54.97 years with SD(±14.18 years). The highest number of patients with hypertension was in 51 to 60 years (25.6%) followed by 41-50 years (21.60%), 31(15.60%) of the patients presented with Hypertensive crises. Conclusion: The prevalence of systemic hypertension was considerably high in our study. Newer and multifaceted approaches along with other effective preventive strategies have to be implemented to raise awareness among the publics regarding risk factors for systemic hypertension and its control. Early detection and proper management of Hypertension including therapeutic lifestyle modifications is the key to success.